Association Between Residential Exposure to Road Traffic Noise and Psychological Health in Preschool Children: Exposure to Road Traffic Noise and Psychological Health: Dėdelė et al. - Dėdelė, Audrius; Nemaniūtė-Gužienė, Jolanta; Gražulevičienė, Regina; Andrušaitytė, Sandra; Miškinytė, Auksė (Journal of Urban Health, 2025)
Environmental noise pollution is one of the biggest concerns and the most important challenges in urban areas. Evidence from epidemiological studies shows that acoustic pollution can impact human health, and the effects may be stronger in susceptible and sensitive individuals. The objective of the study was to determine the individual exposure to road transport noise for preschool children in the residential environment and to assess its impact on children's psychological health. This is the first representative large-scale noise impact study in Lithuania aimed at the psychological health of children. A total of 1457 parent–child pairs were involved in the study. Residential exposure to environmental noise caused by road transport in Kaunas agglomeration, Lithuania was determined by applying geographic information systems and strategic noise mapping. A standardized Strengths and Difficulties Questionnaire (SDQ) was used to assess psychological health problems in children. Multivariate logistic regression analysis was used to determine the association between residential exposure to environmental noise caused by road transport and children's psychological health. The results of the study showed that the risk of hyperactivity and total scale difficulties increased statistically significantly up to 77% and up to 48%, respectively, in the highest noise (L ≥ 50 dB) exposure. The obtained results provide new knowledge about the relationship between road traffic noise in the residential environment and the psychological health of preschool children.